Nursing from the perspective of Decent Work. - Quintana Zavala, María Olga; Valenzuela Suazo, Sandra; Paravic Klijn, Tatiana (Enfermería Global)
Introduction: The International Labor Organization encourages improvement in the quality of life for workers, highlighting poor working conditions and promoting Decent Work for all. Objective: To reflect on the implications of the work of nursing in relation to the concept of Decent Work. Development: Decent Work responds to the increasing vulnerability of workers, mainly young people, women and the poor. Nursing as a profession is made up mostly of women, faces multiple occupational hazards, including psychosocial risk factors, biological, physical, chemical and ergonomic, which means that this health care profession has higher health risks, is not the best paid job, nor is well recognized socially around the world. Conclusion: Decent Work involves competitive salaries, social security, fair globalization, education, gender equality, low risk, with labor rights and fairness. Nursing professionals, health institutions and governments should reconsider attending to the multiple risks that are faced in any hospital to make nursing work comply with all the features of Decent Work, promoting the reduction of occupational hazards and providing better salaries and working conditions in general to all nurses and improving the quality of their working life.